2018
DOI: 10.1186/s12939-018-0845-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations of acute conflict with equity in maternal healthcare: an uncontrolled before-and-after analysis of Egypt demographic and health survey data

Abstract: BackgroundEquity of usage of maternal services during conflict is considered key to reducing maternal health risks globally. However, evidence showing how conflict affects maternal care use among different population groups is minimal. This study examined how the Egyptian acute conflict of 2011–2012 affected maternal care use among different socioeconomic, demographic, and geographic groups.MethodsAn ‘uncontrolled before-and-after’ study design was used to perform multi-level modelling regression analysis on 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The conflict in the Casamance region in the south of Senegal may explain the unchanged subnational equity gap in FBD due to limited access to health facilities to seek care including delivery. A study conducted for the populations of Uganda and Egypt found that coverage of FBD tended to be lower in areas with civil unrest as access to transport and delivery services became limited [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The conflict in the Casamance region in the south of Senegal may explain the unchanged subnational equity gap in FBD due to limited access to health facilities to seek care including delivery. A study conducted for the populations of Uganda and Egypt found that coverage of FBD tended to be lower in areas with civil unrest as access to transport and delivery services became limited [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The conflict in the Casamance region in the south of Senegal may explain the unchanged subnational equity gap in FBD due to limited access to health facilities to seek care including delivery. A study conducted for the populations of Uganda and Egypt found that coverage of FBD tended to be lower in areas with civil unrest as access to transport and delivery services became limited (40,41).…”
Section: Discussionmentioning
confidence: 99%